Examining Trends in Obstetric Quality Measures for Monitoring Health Care Disparities. Issue 6 (June 2018) - Janevic, Teresa; Egorova, Natalia N.; Zeitlin, Jennifer; Balbierz, Amy; Hebert, Paul L.; Howell, Elizabeth A.
Abstract : Background: Elective delivery (ED) before 39 weeks, low-risk cesarean delivery, and episiotomy are routinely reported obstetric quality measures and have been the focus of quality improvement initiatives over the past decade. Objective: To estimate trends and differences in obstetric quality measures by race/ethnicity. Research Design: We used 2008–2014 linked birth certificate–hospital discharge data from New York City to measure ED before 39 gestational weeks (ED <39), low-risk cesarean, and episiotomy by race/ethnicity. Measures were following the Joint Commission and National Quality Forum specifications. Average annual percent change (AAPC) was estimated using Poisson regression for each measure by race/ethnicity. Risk differences (RD) for non-Hispanic black women, Hispanic women, and Asian women compared with non-Hispanic white women were calculated. Results: ED<39 decreased among whites [AAPC=−2.7; 95% confidence interval (CI), −3.7 to −1.7), while it increased among blacks (AAPC=1.3; 95% CI, 0.1–2.6) and Hispanics (AAPC=2.4; 95% CI, 1.4–3.4). Low-risk cesarean decreased among whites (AAPC=−2.8; 95% CI, −4.6 to −1.0), and episiotomy decreased among all groups. In 2008, white women had higher risk of most measures, but by 2014 incidence of ED<39 was increased among Hispanics (RD=2/100 deliveries; 95% CI, 2–4) and low-risk cesarean was increased among blacks (RD=3/100; 95% CI, 0.5–6), compared with whites. Incidence of episiotomy was lower among blacks and Hispanics than whites, and higher among Asian women throughout the study period. Conclusions: Existing measures do not adequately assess health care disparities due to modest risk differences; nonetheless, continued monitoring of trends is warranted to detect possible emergent disparities.